2022
DOI: 10.1101/2022.04.19.488762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural Basis of MicroRNA Biogenesis by Dicer-1 and Its Partner Protein Loqs-PB

Abstract: SUMMARYIn animals and plants, Dicer enzymes collaborate with double-stranded RNA-binding proteins to convert precursor-microRNAs (pre-miRNAs) into miRNA duplexes. We report six cryo-EM structures of Drosophila Dicer-1 and its partner Loqs-PB. The structures show Dicer-1•Loqs-PB (1) before binding pre-miRNA, (2) after binding and in a catalytically competent state, (3) after nicking one arm of the pre-miRNA, (4) following complete dicing and initial product release. Our reconstructions suggest that pre-miRNA bi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 106 publications
1
3
0
Order By: Relevance
“…Our newly resolved 3D structure of pre-miR-31 in its processing-competent conformation and elucidation of its intrinsic regulatory mechanism informs on the important role that pre-miR apical loop plasticity plays in controlling Dicer processing. Our structural and biochemical studies are consistent with proposed models of pre-miR processing based on cryo-EM structures of human Dicer [59] and fly Dicer-1 [60] bound with pre-miRs. The pre-let-7 bound human Dicer structure revealed that the pre-let-7 RNA adopts multiple conformations [59] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our newly resolved 3D structure of pre-miR-31 in its processing-competent conformation and elucidation of its intrinsic regulatory mechanism informs on the important role that pre-miR apical loop plasticity plays in controlling Dicer processing. Our structural and biochemical studies are consistent with proposed models of pre-miR processing based on cryo-EM structures of human Dicer [59] and fly Dicer-1 [60] bound with pre-miRs. The pre-let-7 bound human Dicer structure revealed that the pre-let-7 RNA adopts multiple conformations [59] .…”
Section: Discussionsupporting
confidence: 89%
“…This hypothesis is consistent with our findings that the pre-miR-31 large apical loop structure is the preferred substrate for Dicer binding, but that the structure with a cinched junction region is a “dicing-competent” structure. The recent cryo-EM structures of fly Dicer-1 reveal further details of the Dicer-1-pre-miR structure in the “Dicing” state [60] . In the “Dicing” structure, the dicing activity of Dicer-1 is inhibited by replacing Mg 2+ with Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…In D. melanogaster, DCR-1 is indispensable for miRNA biogenesis, whereas DCR-2 is responsible for generating endogenous and exogenous siRNAs, despite both enzymes possessing RNase III enzyme activity (Lee et al, 2004). DCR-1 interacts with Loquacious (Loqs), composed of three double-strand RNAbinding domains that regulate the efficiency of mature miRNA processing (Fukunaga et al, 2012;Jouravleva et al, 2022;Liu et al, 2007). Dic-2 in complex with its partner, R2D2, forms an RNA-induced silencing complex (RISC) loading complex, binds to a perfectly complementary siRNA and is sorted into AGO2 (Liu et al, 2009;Pham et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The biogenesis pathway in animals starts within the nucleus with the processing of the primary miRNA (pri-miRNA) by the microprocessor complex composed of RNase type III Drosha and its partner protein Pasha (known as DGCR8 in vertebrates) (Han et al , 2004a). The resulting pre-miRNA is transported by Exportin 5 into the cytoplasm where it gets cleaved into the mature miRNA by the RNase type III Dicer with the help of partner double-stranded RNA binding proteins such as Loqs and TRBP (Förstemann et al , 2005; Jouravleva et al , 2022; Fareh et al , 2016; Redfern et al , 2013; Wilson et al , 2015). In plants, both pri-miRNA and pre-miRNA are processed within the nucleus by DICER-LIKE1 (DCL1) assisted by its partner protein Hyponastic Leaves1 (HYL1) (Voinnet, 2009; Han et al , 2004b).…”
Section: Introductionmentioning
confidence: 99%